2018
DOI: 10.1111/sed.12412
|View full text |Cite
|
Sign up to set email alerts
|

Variable character and diverse origin of hybrid event beds in a sandy submarine fan system, Pennsylvanian Ross Sandstone Formation, western Ireland

Abstract: Hybrid event beds comprising both clean and mud‐rich sandstone are important components of many deep‐water systems and reflect the passage of turbulent sediment gravity flows with zones of clay‐damped or suppressed turbulence. ‘Behind‐outcrop’ cores from the Pennsylvanian deep‐water Ross Sandstone Formation reveal hybrid event beds with a wide range of expression in terms of relative abundance, character and inferred origin. Muddy hybrid event beds first appear in the underlying Clare Shale Formation where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 101 publications
(230 reference statements)
6
129
0
Order By: Relevance
“…Hybrid event beds (Haughton et al, 2003(Haughton et al, , 2009) are most commonly identified toward the bases and fringes of lobe deposits (e.g., Hodgson, 2009;Talling, 2013). However, they can form in any environment where mud and mudstone clasts are entrained into the turbulent flow, damping turbulence, and developing high-concentration to pseudo-laminar flow conditions (e.g., Ito, 2008;Haughton et al, 2003;Talling et al, 2004;Baas et al, 2011;Pierce et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid event beds (Haughton et al, 2003(Haughton et al, , 2009) are most commonly identified toward the bases and fringes of lobe deposits (e.g., Hodgson, 2009;Talling, 2013). However, they can form in any environment where mud and mudstone clasts are entrained into the turbulent flow, damping turbulence, and developing high-concentration to pseudo-laminar flow conditions (e.g., Ito, 2008;Haughton et al, 2003;Talling et al, 2004;Baas et al, 2011;Pierce et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The lower portion of the succession, the Shannon Group ( Fig. 1B; Clare Shale, Ross Sandstone and Gull Island formations), represents deep-marine and slope depositional environments (Hodson & Lewarne, 1961;Rider, 1974;Gill, 1979;Chapin et al, 1994;Wignall & Best, 2000Lien et al, 2003;Martinsen et al, 2003Martinsen et al, , 2017Pyles & Jennette, 2009;Pyles et al, 2011Pyles et al, , 2014Pierce et al, 2018). The Pennsylvanian (Namurian) Central Clare Group overlies these deposits ( Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…The shallow channelized turbidite beds are interpreted as representing the down‐dip termination of distributary channels (Johnson et al, ; Terlaky, Rocheleau, & Arnott, ). There is increasing evidence that gravity flow transformations, from turbidity flow to cohesive and laminar flow, are the dominant bed type in the distal ends of submarine fan systems and the fringes of individual lobes (e.g., Barker, Haughton, McCaffrey, Archer, & Hakes, ; Fonnesu et al, ; Grundvåg et al, ; Haughton et al, , ; Hodgson, ; Ito, ; Kane & Pontén, ; Lowe & Guy, ; Pierce et al, ; Spychala, Hodgson, & Lee, ; Sylvester & Lowe, ; Talling et al, ). However, they are not exclusively restricted to the distal parts and can also be present in proximal areas of lobes, where they are interpreted as the product of enhanced erosion and flow deceleration due to processes occurring in the channel‐lobe transition and due to basin confinement (e.g., Fonnesu et al, ; Haughton et al, ; Ito, ; Jackson et al, ; Mueller et al, ; Patacci et al, ; Sylvester & Lowe, ; Terlaky et al, ; Vinnels, Butler, McCaffrey, & Lickorish, ).…”
Section: Bed Type Associations (Bta)mentioning
confidence: 99%
“…The predominance of the mudstone bed type (BT1), the mainly dm-scale thickness of individual sandstone beds and the absence of bed amalgamation, indicates a more basinward or lateral position relative to BTA 2. At the individual lobe scale, hybrid event beds are common elements of the lobe fringe area (Fonnesu et al, 2018;Grundvåg et al, 2014;Haughton et al, 2003Haughton et al, , 2009Hodgson, 2009;Ito, 2008;Kane & Pontén, 2012;Pierce et al, 2017;Spychala, Hodgson, & Lee, 2017;Talling et al, 2004). Bed thinning upward patterns may indicate either lobe/fan retreat (i.e., retrogradation), across-strike lobe/fan shifting (i.e., avulsion), or a combination of both (Prélat & Hodgson, 2013;Spychala, Hodgson, & Lee, 2017).…”
Section: Bed Type Associations (Bta)mentioning
confidence: 99%